The Role of Soft Skills in Improving the Job Readiness of Study Program Graduates: A Study on Critical Thinking in Accounting Education, Faculty of Economics and Business, Universitas Putra Indonesia YPTK - Putri, Yonna; Seplinda, Mutia; Hermalia, Hermalia (Journal of English Language and Education, 2025)
This study aims to identify the influence of soft skills (about critical thinking) on the work readiness of accounting graduates of the Faculty of Economics and Business, Universitas Putra Indonesia YPTK Padang. In this study, soft skills about critical thinking function as an independent variable (X), while work readiness is the dependent variable (Y). The population studied included all students of the accounting study program, class of 2021, totaling 150 students. The sampling method used was purposive sampling, so that the sample in this study consisted of 100 respondents. Data were collected through questionnaires and documentation, and data analysis was carried out using descriptive percentage analysis, instrument testing, and hypothesis testing. Instrument testing includes validity testing and reliability testing, while hypothesis testing includes simple linear regression testing, coefficient of determination (R²) testing, and t-testing. The results of the simple regression analysis show the equation Y = 36.924 + 0.143X, which means that if the soft skill value is zero, then the work readiness will reach 0.143. From the results of data processing and analysis that have been carried out, it can be concluded that soft skills have a positive influence of 0.143 on the work readiness of accounting graduates of the Faculty of Economics and Business, Putra Indonesia University YPTK Padang.